(untitled) (Fiep Bulletin - online, 2015)
The study aimed to investigate the influence of physical activity on the quality life of elderly, based on the factor self-esteem, psycho social and socialization process of a seniors group in SãoLuís, Maranhão. Was used a methodology based on the quantitative and qualitative research, characterized for a descriptive and exploratory study. The sample population consisted of 30 elderly between 60 and 75 years, played his activities activities twice a week from 7am to 8am. As an instrument for data collection, a questionnaire Quiles and Espada (2010) was applied to measure the degree of self-esteem and a semistructured interview. The results showed that, in the elderly group, there were positive results between the level of social relationships and self-esteem. Physical activities were very important in mitigating the evils of the aging process. It was realized that the practice of activities is an element of strong influence for improving the quality of life and health of the elderly. One realizes that the practice of activities is an element of strong influence for improving the quality of life and health of the elderly.